Cambio de paradigmas en la educación básica regular - Zilberman, Jack (2018)
Education plays a fundamental role in the political, economic and social development of a nation.  It provides for the possibility for escaping poverty and for participating actively and fully in society and in the marketplace. In general terms, the Government has assumed the responsibility for providing and financing basic education.  However, due to its breadth, this responsibility is very complex.  It ́s required, therefore, a paradigm shift. This essay explains that public-private partnerships (PPP) have emerged in response to this requirement. Different models consider separating the financing from the provision of educational services, as an alternative for increasing access and improving quality, for which “Fe y Alegria” schools, and “High Performance Schools” (COAR), constitute but two examples to cite and emulate